Influence of casting conditions and alloy additives on the Zn40Al2Cu alloy structure - Michalik, R; Tomaszewska, A; Woźnica, H (IOP conference series. Materials Science and Engineering, 2011)
Zn-Al-Cu alloys are characterized by several advantageous properties that can include good castability, good tribological properties, and low energy value needed to form the product. In comparison to bronzes, Zn-Al-Cu alloys are characterized by a lower density. The purpose of this study was to determine the effect of casting conditions and the addition of silicon and rare earth elements on the structure of a Zn-40%Al alloy. The subjects of this examination were an unmodified alloy, an alloy with the addition of 1,5% Si, and an alloy with additions of 1,5%Si and rare earth elements. Samples were cast in sand and graphite molds. In order to determine the microstructure of the tested samples, metallographic examinations using a light microscope and a scanning electron microscope with energy dispersive spectroscopy (EDS) through an X-ray spectrometer were used.